Troglitazone: Recent Approach to Type-II diabetes - A. Siddiqui, Anees (Asian Journal of Chemistry, 2010)
Diabetes mellitus is a fairly common metabolic disease, characterized by hyperglycaemia due to lack of insulin secretion from beta cells in the islets of langerhans.